The Influence of Leadership, Individual Abilities and Training on Employee Performance (Study at the North Sumatra Provincial DPMPTSP Office) - Kemit, Golongan; Dirgantara, I Made Bayu; Noviyanti, Mery (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the influence of leadership, individual abilities, and training on employee performance at the Investment and One-Stop Integrated Services Office (DPMPTSP) of North Sumatra Province. This study uses a quantitative method with a multiple linear regression analysis model to test the relationship between independent and dependent variables. The hypothesis tested in this study is that leadership, individual abilities, and training have a significant effect on employee performance. The research sample consisted of 86 Civil Servants working at the DPMPTSP of North Sumatra Province. The results showed that leadership, individual abilities, and training had a positive and significant effect on employee performance, respectively, with coefficient values of 0.351, 0.374, and 0.320, respectively. Statistical tests showed that the three independent variables had a T-statistical value of > 1.96 and a P-value of < 0.05, so the hypothesis was accepted. An R-Squares value of 0.815 indicates that leadership, individual ability, and training together explain 81.5% of the variation in employee performance. In addition, the Q-Squares value of 0.611 indicates that this model has good predictability.